PENGARUH SISTEM E-FILLING, SANKSI DAN PENGETAHUAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DENGAN AKHLAK SEBAGAI VARIABEL MODERATING (Studi Kasus UMKM Asal Wangi-Wangi) - Khairum Nadila Sandy; Lince Bulutoding; Raodahtul Jannah (Academic Bright Collaboration, 2024)
This study aims to examine the influence of the e-filing system, sanctions and knowledge on the compliance of MSME taxpayers with morals as a moderating variable with a case study of MSMEs from Wangi-Wangi which are registered at the Bau-Bau KPP. This study uses a quantitative methodology with a causal associative type as the methodology of this research. The theories used in this study are TAM (Technology Acceptance Model) theory and attribution theory. MSME taxpayers from Wangi-Wangi who are registered at the Bau-Bau KPP are the population of this study. The technique used in collecting nonprobability sampling is by using the purposive sampling approach. Respondents were given a questionnaire as part of the data collection procedure. There were 45 respondents whose data was successfully collected, to find out the impact of each variable, this study used multiple linear regression analysis and moderate regression analysis. The results of the multiple linear analysis show that the variables of the e-filling system, sanctions and knowledge have a positive effect on the corruption of MSME taxpayers. The moderating variable, namely morals, can only moderate the influence of sanctions on the compliance of MSME taxpayers, while morals cannot moderate the influence of the e-filling system and knowledge on the compliance of MSME taxpayers.